Individual Treatment of Delayed Distal Biceps Tendon Rupture: Case Report and Literature Review. Issue 3 (March 2019) - Yao, Chenglun; Weng, Weidong; Zhou, Xijie; Poonit, Keshav; Yang, Jingquan; Lin, Damu; Sun, Chao; Yan, Hede
Abstract : Introduction: Complicated elbow injuries (elbow injuries with bone and soft tissue injury) with distal biceps tendon ruptures (DBTRs) are not uncommon. There are several treatment modalities in different situations of injuries. In this article, we reported 3 successful individual treatments of delayed DBTR with complicated elbow injuries. Materials and Methods: Three cases of complicated elbow injuries treated between 2010 and 2016 were reviewed. The delayed DBTR cases were summarized and treated. Mayo Elbow Performance Score value, range of motion, and visual analog scale score were used to assess outcomes after a minimum follow-up of 12 months. Results: All 3 patients were male, aged 47 to 54 years (mean, 49.6 years). Patients received surgical treatments. After a mean follow-up of 13.7 months, in cases 1 and 2, Mayo Elbow Performance Score values improved by 50% and 100%, elbow flexion-extension arc were 115 degrees and 110 degrees, pronation-supination arc were 130 degrees and 120 degrees. Arthrodesis case reported pain relief; visual analog scale score for pain was 0 to 1. No postoperative complications were observed, and all patients were satisfied with the results. Conclusions: Individual treatment is advised in DBTR with complicated elbow injuries. Secondary treatment of DBTR can achieve satisfactory results using individual strategies depending on patients' overall condition.